Investigating the Factors Affecting the Sleep of Babies Between 0-2 Years of Age - Ayşıl Seda Akar; İbrahim Haluk Yavuzer (Çocuk Dergisi)
Objective: This research has been carried out to investigate the factors affecting the sleep of babies between 0-2 years of age.Materials and Method: The participants of the study are composed of 60 mothers with babies between the ages of 0-2 years who applied to a family health center in the Beykoz district of Istanbul Provincial Health Directorate to have their children or themselves examined or treated. The research is a descriptive study that uses the convenience sampling technique. The researcher and advisor prepared two forms for use in the study. The questions on the Parent-Baby Information Form are intended for learning the parents’ and babies’ sociodemographic information, and the Mother Interview Form contains qualitative and quantitative questions that were prepared to collect information about the factors affecting their babies’ sleep patterns. The research findings were obtained using mixed methods and analyzed using the program SPSS. Frequency analyses and chi-squared tests were also used to analyze the data. The analysis results consider p values less than 0.05 (p ≤ 0.05) to be statistically significant.Results: The mothers were mostly determined to simultaneously regulate the environmental sounds and lights in their babies’ sleep environment, with the majority of them putting their babies in their cribs in the same room as them. The study learned that the majority of mothers accompany their babies when they go to sleep, and most of the babies have difficulty falling asleep at night. Most of the babies were determined to fall asleep at night by suckling on their mother’s breast and to prefer a pacifier as a sleeping aid after falling asleep at night. According to the research results, when comparing the babies’ sleeping positions at monthly intervals, a statistically significant difference was seen to occur between them (p=0.025).Conclusion: The study results reflect the perceptions of the mothers in the sample group regarding their babies’ sleep patterns, sleep routines, sleep environments, and sleep hygiene. In addition, the chi-squared results showed the monthly intervals to affect the babies’ sleep positions.